Current perspective on rituximab in rheumatic diseases - Schioppo T; Ingegnoli F (Dove Medical Press, 2017)
Tommaso Schioppo, Francesca Ingegnoli Department of Clinical Sciences and Community Health, Division of Rheumatology, ASST Pini, Università degli Studi di Milano, Milano, Italy Abstract: The steadily increasing knowledge regarding pathogenetic mechanisms in autoimmune rheumatic diseases has paved the way to different therapeutic approaches. In particular, the market entry of biologics has dramatically modified the natural history of rheumatic chronic inflammatory diseases with a meaningful impact on patients’ quality of life. Among the wide spectrum of available biological treatments, rituximab (RTX), first used in the treatment of non-Hodgkin’s lymphoma, was later approved for rheumatoid arthritis and anti-neutrophil cytoplasmic antibodies-associated vasculitis. Nowadays, in rheumatology, RTX is also used with off-label indications in patients with systemic sclerosis, Sjögren’s syndrome and systemic lupus erythematosus. RTX is a monoclonal antibody directed to CD20 molecules expressed on the surfaces of pre-B and mature B lymphocytes. It acts by causing apoptosis of these cells with antibody- and complement-dependent cytotoxicity. As inflammatory responses to cell-associated immune complexes are key elements in the pathogenesis of several autoimmune rheumatic diseases, such an approach might be effective in these patients. In fact, RTX, by promoting the rapid and long-term depletion of circulating and lymphoid tissue-associated B cells, leads to a lower recruitment of these effector cells at sites of immune complex deposition, thus reducing inflammation and tissue damage. RTX is of the most interest to rheumatologists as it represents an important additional therapeutic approach. Thus, the advent in clinical practice of approved RTX biosimilars, such as CT-P10, may be of help in improving treatment access as well as in reducing costs. Keywords: rituximab, rheumatoid arthritis, ANCA-associated vasculitis, systemic sclerosis, Sjögren’s syndrome, systemic lupus erythematosus, biologics, biosimilars, myositis, pregnancy, vaccination